As tendências adaptadas as variáveis antropométricas: produtos de moda auxiliando na satisfação corporal - Ranieri, Isabele Bedin (2017)
Women’s gargments are abundant in the market, in all shapes, colors and sizes, but brands don’t care about the type of the body of their consumers, and can cause discomfort when purchasing a product. Unsatisfied customers are left with negative brand image, not returning in the next purchase. This paper seeks to study the different biotypes of Brazilian women, to develop models adapted to each silhouette and to elaborate pieces that are trend and help the consumer to be satisfied with their image, product and brand. It is expected that the adapted modeling satisfact the customers of each biotype but not preventing them of use the recommended clothes to other kind of body different of yours.